Directions encouraging banks in financing innovation sector - Rakhmetova, А.М.; Kurmanalina, А.K.; Gusmanova, J.A.; Yerzhanova, S.K. (BUKETOV BUSINESS REVIEW, 2017)
This article examines the issues of limited participation of commercial banks in the development of innovations in the real sector of the economy. In the course of the study based on the analysis of the influence of internal and external factors on the process of interaction of Bank and real sectors of the economy, identified key problems that hinder active Bank participation in the financing of innovation in the real sector. In particular, the problems are concentrated in the areas of resourcing, high-level financial and industry risks and imperfection of the mechanism of regulation of the banking and real sectors of the economy. It is concluded that no combination of regulation and incentives in a single package against entities in both the banking and real sectors, working in the innovation sector, to address existing barriers to harmonious interaction is not possible. In this regard, the article offers recommendations involving the implementation of measures of the state in improving the institutional environment of interaction of Bank and real sectors of the economy in the innovation sector, including through the use of public-private partnerships, tax and price incentives to the most active participants.